"The tablet is on the table!" The need for a teachers' self-hetero-eco technological formation program. Issue 4 (3rd August 2015) - Freire, Maximina Maria
Abstract : Purpose: – The Federal Government has begun distributing tablets to teachers in public schools in Brazil. However, no preparation was provided to guide professionals on how to use them for pedagogical purposes. As a result, teachers have been carrying tablets around or leaving them alone on their classroom tables. Considering this situation, the purpose of this paper is to discuss the possibility of adopting a ternary conception of formation processes – the self-hetero-eco formation process – to help teachers learn how to use tablets for educational purposes; and on the potential of such a process to congregated teachers in the joint creation and maintenance of a Didactic Digital Material/App Data Bank. Design/methodology/approach: – Theoretically, this paper is grounded on complexity principles (Morin, 2008, 2010), and especially on the studies made by Moraes (2007), Freire (2009) and Freire and Leffa (2013). Findings: – The movement of perceiving each teacher as responsible for his/her formation (personalization), interacting with others to expand possibilities, co-constructing knowledge to reach co-formation (socialization), and interacting with the environment with/from which s/he learns (ecoligization) will reveal the self-hetero-eco technological formation process which may help teachers create steady links amongst themselves at school and resolve many difficult situations such as the need to overcome the lack of technological skills to use tablets. Besides that, the idea of joining teachers together and jointly creating and maintaining a Didactic Digital Material/App Data Bank may not only impact on the use of the tablet itself but also on interpersonal relationships, intensifying respect, companionship and friendship, among other important ties that help bind people together. Originality/value: – This paper presents an innovative formation concept which is not based on time development, but which is based on the agents involved in the process and in the environment where the formation takes place. This concept is based on complexity and seems to be more attuned to the features of the contemporary world.